Pengenaan Pajak Penghasilan (PPH) atas Peralihan Hak atas Tanah atau Bangunan - I Ketut Gede Purnayasa; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Preferensi Hukum, 2021)
The imposition of income tax on land and buildings is the imposition of tax with applicable provisions and is carried out by individuals or legal entities. The purpose of this study is to reveal the regulation regarding the imposition of income tax on the transfer of rights to land and or buildings and the mechanism for imposing income tax on the transfer of rights to land and or buildings. The research method used is normative legal research with a statutory approach and a conceptual approach. The sources of legal materials used are primary, secondary and tertiary sources of legal materials. The materials that have been obtained are then analyzed using qualitative analysis techniques where the assessment is carried out deductively, in order to produce data that is descriptive analytical. The results of the study reveal that the regulation regarding the imposition of income tax on land and buildings is carried out in accordance with the provisions in Article 4 paragraph (2) letter (d) of the Income Tax Law, in which the imposition of taxes is absolute. On this basis, the imposition of income tax including the nature, amount and procedure for its payment, as well as its withholding and collection is regulated by PP. 71 Year 2008. And the mechanism of imposition of taxes has been regulated in PP no. 34 of 2016 especially in article 2 paragraph (1).